2022
DOI: 10.3389/fpls.2022.866404
|View full text |Cite
|
Sign up to set email alerts
|

Loss of OsEAF6, a Subunit of the Histone Acetyltransferase Complex, Causes Hybrid Breakdown in Intersubspecific Rice Crosses

Abstract: Gene duplication plays an important role in genetic diversification, adaptive evolution, and speciation. Understanding the mechanisms and effects of postzygotic isolation genes is important for further studies of speciation and crop breeding. The duplicate recessive genes hwe1 and hwe2 cause hybrid breakdown, characterized by poor vegetative growth and reproductive dysgenesis in intersubspecific crosses between Oryza sativa ssp. indica and japonica. Using a map-based cloning strategy, we found that HWE1 and HW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Additionally, the HWS2 copy number varies among Asian rice accessions (Supplementary Data 1), suggesting that such genetic model with the parallel divergence lineage is equally applicable to explain the subspecific RI. Unlike previously identified duplicated genes conditioning semi-sterility of rice hybrids: DPL1/2 16 , S27/S28 17 , and DGS1/2 19 , HWS1/2 serve as indispensable epigenetic modifiers required for cell fate in both reproductive and vegetative organ development, causing developmental defect and complete sterility in the F 2 or the later generation once the reciprocal gene loss occurs 53 . Despite the fact that the identical recessive genes hwe1/2 have been reported, the present results have expanded the applicability of the EAF6-mediated hybrid sterility model to a wider base of inter-subspecific incompatibility, and revealed that the metabolic disorder of biotin and fatty acid may contribute to the sterility phenotype other than the common autoimmune response in hybrids.…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, the HWS2 copy number varies among Asian rice accessions (Supplementary Data 1), suggesting that such genetic model with the parallel divergence lineage is equally applicable to explain the subspecific RI. Unlike previously identified duplicated genes conditioning semi-sterility of rice hybrids: DPL1/2 16 , S27/S28 17 , and DGS1/2 19 , HWS1/2 serve as indispensable epigenetic modifiers required for cell fate in both reproductive and vegetative organ development, causing developmental defect and complete sterility in the F 2 or the later generation once the reciprocal gene loss occurs 53 . Despite the fact that the identical recessive genes hwe1/2 have been reported, the present results have expanded the applicability of the EAF6-mediated hybrid sterility model to a wider base of inter-subspecific incompatibility, and revealed that the metabolic disorder of biotin and fatty acid may contribute to the sterility phenotype other than the common autoimmune response in hybrids.…”
Section: Discussionmentioning
confidence: 68%
“…HWE1 and HWE2 encode the Esa1-associated factor 6 (EAF6) protein, which is a component of histone acetyltransferase complexes and possibly plays a pivotal role in the transcriptional regulation of essential genes for plant development. hwe1 and hwe2 alleles lack the function and cause hybrid breakdown not resulting from autoimmune response ( Kubo et al., 2022 ).…”
Section: Hybrid Seedling Lethalitymentioning
confidence: 99%